2002
DOI: 10.1186/1471-2156-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundPolymorphisms in the gene that encodes the human cellular receptor for group B coxsackieviruses and adenoviruses (HCAR) could be responsible for differences in susceptibility to infections with these pathogens. Moreover, adenovirus subgroup C-mediated gene therapy could be influenced by mutations in the coding exons for the aminoterminal immunoglobulin-like 1 (Ig1) domain, which is the essential component for adenovirus fiber knob binding.ResultsUsing two primersets in the adjacent intron sequences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Wu et al 15 shows that 700–1000 SNPs were necessary to robustly estimate the genetic difference among subpopulations, our result shows that about 5000 tagSNPs and haplotype loci derived from them are suitable for population structure analysis and germplasm study. In maize and many other organisms, it has also been reported that haplotype loci derived from tagSNPs are more informative than binary SNPs 16 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al 15 shows that 700–1000 SNPs were necessary to robustly estimate the genetic difference among subpopulations, our result shows that about 5000 tagSNPs and haplotype loci derived from them are suitable for population structure analysis and germplasm study. In maize and many other organisms, it has also been reported that haplotype loci derived from tagSNPs are more informative than binary SNPs 16 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies in various ethnic populations demonstrate that effect of this mutation on body mass is more complex. An association of Ala12 variant with decreased adiposity is confirmed in diabetic, nondiabetic, or healthy subjects [ 53 58 ]. In studies involving an African American population and a white American population, this mutation is associated with lower BMI in African Americans and increased BMI in white Americans [ 59 , 60 ], indicating that same genetic mutation results in different responses in different ethnic groups.…”
Section: Effect Of Ppar γ 2 Pro12alamentioning
confidence: 99%
“…Since the first whole plant genome to be sequenced [ 27 ], de novo and reference-based SNP discovery and application are now feasible for numerous plant species. Large-scale SNP discovery was performed in almost all sequenced plant genomes such as maize [ 28 ], Arabidopsis [ 29 ], rice [ 30 ], rapeseed [ 31 ], potato [ 32 ], and pepper [ 33 ]. On the method side, Genotyping-By-Sequencing (GBS) has recently emerged as a promising genomic approach to explore plant genetic diversity on a genome-wide scale [ 34 ], followed by the more cost-effective Genotyping-in-Thousands by sequencing (GT-seq) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%